A polynomial regression model for stabilized turbulent confined jet diffusion flames using bluff body burners - Tahani S. Gendy; Taher M. El-Shiekh; Amal S. Zakhary (Egyptian Journal of Petroleum)
Thermal structure of stabilized confined jet diffusion flames in the presence of different geometries of bluff body burners has been mathematically modeled. Two stabilizer disc burners tapered at 30° and 60° and another frusted cone of 60°/30° inclination angle were employed all having the same diameter of 80 (mm) acting as flame holders. The measured radial mean temperature profiles of the developing stabilizing flames at different normalized axial distances were considered as the model example of the physical process. A polynomial mathematical model of fourth degree has been investigated to study this phenomenon to find the best correlation representing the experimental data. Least Squares regression analysis has been employed to estimate the coefficients of the polynomial and investigate its adequacy. High values for R2 > 0.9 obtained for most of the investigated bluff burners at the various locations of x/dj prove the adequacy of the suggested polynomial for representing the experimental results. Very small values of significance F < (α = 0.05) for all investigated cases indicate that there is a real relationship between the independent variable r and the dependant variable T. The low values of p < (α = 0.05) obtained reveal that all the recorded parameters for all the investigated cases are significant.